Kajian Etnobotani dan Inventarisasi Tanaman Obat Berbasis Kearifan Lokal Masyarakat Desa Harjomulyo Jember - Bayuda Luqman Al Farisi; Zakiyatul Firdausiyeh Az Zahro; Akhmad Ferdiansyah (Program Studi Pendidikan Biologi, 2026)
An ethnobotanical exploration of medicinal plants was conducted as a strategic step to document and classify the diversity of plants integrated into traditional healing systems. This study aimed to identify species diversity, log the specific plant organs extracted, and map the processing methods of medicinal plants by the local community in Harjomulyo Village, Silo District, Jember Regency. Utilizing a qualitative approach with an exploratory descriptive design, this field investigation was carried out in April 2023, focusing on Sumber Lanas Barat and Sumber Lanas Timur hamlets. A total of 30 key informants were selectively determined through a purposive sampling technique based on their deep traditional knowledge, active usage, or conservation practices of medicinal plants. Primary data gathering combined observation, semi-structured interviews, questionnaires, and digital documentation. The inventory successfully recorded 45 species of medicinal vegetation distributed across 32 taxonomic families. The Zingiberaceae family emerged as the most dominant taxa utilized, with turmeric (Curcuma domestica) being the most heavily integrated species (19%). Furthermore, leaves were identified as the most exploited anatomical organ (42%), with boiling being the most preferred preparation technique adopted by the local community (64%).